How Later Adolescents With Adult Responsibilities Experience HIV Bereavement in Nigeria: Application of a Bereavement Model. (September 2015) - Popoola, Tosin; Mchunu, Gugu
Abstract : N/A: Conceptual models assist in the better understanding of phenomena and also in the planning of effective responses. We applied the Dual Process Model (DPM) to examine how six later adolescents (ages 18‐24 years) experienced the multiple stressors of bereavement, maturational tasks, and caregiving roles. Using a semi‐structured interviewing approach, participants who were purposively recruited narrated how parental loss to HIV impacted their lives. In relation to the proposition of the DPM model, the study revealed that participants (a) anticipated grief before the death of their parents, (b) engaged in activities to return to normalcy after parental loss, and (c) neglected grief emotions in order to cope with the demands of caregiving. The application of a model to examine responses to bereavement can assist health care practitioners to appreciate and have a deeper understanding of how best to approach caring interventions for late adolescents with multiple stressors.